Mitigating methane emissions and promoting acetogenesis in ruminant livestock - Mrutu, Rehema Iddi; Abdussamad, Abdussamad Muhammad; Umar, Kabir Mustapha; Abdulhamid, Adnan; Farny, Natalie G. (Frontiers in Animal Science, 2025)
Through enteric fermentation, ruminants convert fibrous biomass into high-quality proteins like meat and milk. In this process however, methanogenic archaea in the ruminant gastrointestinal tract produce methane, a potent greenhouse gas, from the by-products of enteric fermentation: carbon dioxide and hydrogen. Research in ruminant methane mitigation has been extensive, and over the years has resulted in the development of a wide variety of mitigation strategies ranging from cutting our meat consumption, to breeding low emitting cows, to targeting the rumen microbiome. Methods like promotion of reductive acetogenesis, a natural alternative pathway to methanogenesis in the rumen, are at the forefront of rumen microbiome engineering efforts. However, our inability to make acetogenesis a key hydrogen scavenging process in the rumen have limited these manipulation efforts. Herein we comprehensively review these mitigation strategies, with particular emphasis on mechanisms involving the manipulation of rumen acetogenesis. Such manipulation includes the genetic reprogramming of methanogens for reductive acetogenesis. With the advent of CRISPR-Cas genome editing technologies, the potential exists to transform dominant methane-producing archaea, such as Methanobrevibacter ruminantium, into acetate producing organisms. Acetate can, in turn, be utilized by the animal to increase meat and milk production, thus simultaneously reducing emissions and increasing efficiency. The current status and future challenges of these strategies are discussed. We propose that CRISPR offers a promising avenue for sustainable ruminant farming.